Design and Development of Savonius Vertical Axis Wind Turbine - Abrha Nigusse, Nigusse (ASTU, 2015)
In The Small-Scale Manufacturing Industries, The Purchasing Of Machineries Is A Challenge To Survive In The Current Market Competition. The Under Developed And Developing Countries Needs More Attention On Small Scale Manufacturing Industries Where Machineries Are Limited. These Industries Play A Vital Role With Respect To Economy, Employment And Entrepreneurs Etc. To Any Kind Of Nation. From The Needs And Deeds Of Small-Scale Manufacturing Industries, The Objective Of The Thesis Is Aimed To Design And Fabricate The Fixture That Has Major Impact In Performing Multiple Operations On A Single Machine. The Study Had Been Included A Detail Design Analysis Of Components, Complete Fabrication Process And Feasibility Study Of The Fixture. The Design Methods Used Were Based On The Design Concepts And Stress Analysis. Modeling Was Done Using Catiav5 And Solid Works, Master Cam For Manufacturing And Tesa Rugosoft For Feasibility Study. The Study Was Focused On The Geometrical Configuration And Surface Roughness Tests. Face Milling And Keyway Milling Operations On Aluminum Alloy Workpiece Were Carried Out On Vertical Milling Machine And Conventional Lathe Machine To Check The Practicability Of The Fixture. The Machining Was Done Within Three Stages Of Standard Cutting Parameters, Feed, Depth Of Cut And Spindle Speed. The Test Was Recorded Forty-Eight Times By Adjusting Cutting Parameters. By Taking The Average Value Of Each Step, The Optimal Value For The Best Surface Finish Has Been Determined At 0.01m/Min Feed, 2mm Depth Of Cut And 630rpm Spindle Speed. From The Experimentations, It Is Observed That Surface Roughness Increases With An Increase In Feed Rate And Depth Of Cut. From The Optimal Parameters, The Best Result Of Surface Roughness For The Workpiece Manufactured By Milling Machines Is Ra=1.4217 And For Workpiece Manufactured By Fixture Is Ra=1.6585 Which Are Relatively Similar. Also The Geometrical Configuration Test Of The Keyways Proved That The Fixture Can Perform Similar Work As That Of Milling Machine.
Keywords: Savonius, Renewable Energy, Wind, Wind Turbines, generator, Rotor Blade, CFD